Transformasi Pemikiran Hukum Pidana Islam Terhadap Hukum Pidana Nasional (Analisis Implementatif Jarimah Hudud, Qishash dan Ta’zir) - Budi Dermawan; M. Noor Harisudin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
National Criminal Law is currently felt that it does not fulfil the value of justice, certainty and legal usefulness in people's lives because of the number of criminal acts. That has recently occurred makes the law no longer a social control but instead uses the law as an opportunity to take action. Criminal law, this can be due to the lack of a deterrent effect caused by the criminal law itself. Many attempts have been made to implement Islamic criminal law in Indonesia. Still, it is poorly considered by the community because it is understood that Islamic criminal law is only partially understood. Whereas the purpose of Islamic criminal law is to maintain religion, reason, soul, descent and property for the sake of achieving justice, certainty and actual legal benefits. The focus of the problems in writing this thesis are 1). What are the concepts of Jarimah Qishash, Hudud, and Ta'zir in Islamic Criminal Law? 2). How is the Transformation of Jarimah Qishash, Hudud, and Ta'zir in Islamic Criminal Law Against National Criminal Law in Indonesia? The purpose of this research is to describe the concept of Jarimah Qishash, Hudud, and Ta'zir regarding Islamic Criminal Law. As well as to explain the Transformation of Jarimah Qishash, Hudud, and Ta'zir Against National Criminal Law. To identify some of these problems, this study uses a comparative approach method by comparing Islamic criminal law to national criminal law. Looking for similarities and differences in the two directions. Then combine it with the concepts used, then connect and dialogue with other ideas and then make interpretations and conclusions as a reflection of the author so that in the end, the research conclusions will be obtained.